A Negotiation in Middlemarch. Issue 2 (5th May 2021) - Read, Daniel; Hills, Thomas
Abstract : We analyze a negotiation drawn from George Eliot's great novel Middlemarch: A Study of Provincial Life . Eliot is renowned as a perceptive chronicler of social interaction, and she understood the process of negotiation and its role in the community perhaps as well as anyone. The negotiation in question is between a wealthy banker and a former associate who sets out (or perhaps just ends up) blackmailing him. From this negotiation we draw insights into the importance of preparation and the prenegotiation, empathy, and the fostering of relationships (even when you would prefer not to); and the problems of focusing on one's own BATNA rather than your counterparts'. We consider six key negotiation lessons for the fictional negotiator (and for us) and reflect on the difficulty of negotiations in which one's self‐regard is at issue in addition to material goods. We conclude with a brief account of how both fictional and "nonfictional" negotiations further our understanding of how to learn about and improve negotiation practice.